GIS Analysis & Landslide Susceptibility Mapping (LSM) in Murum Reservoir Region, Sarawak. - Sheng Bong, Yan; Hafiz Zulkifly, Muhammad; Sati Hamonangan Harahap, Indra (International Journal of Engineering and Technology, 2018)
Landslides in Malaysia are mostly triggered by rainfall throughout the years. Therefore, it is important to carry out Landslide Susceptibility mapping (LSM) on high prone areas to minimize the destruction caused by unexpected landslides events. Landslides around Murum Reservoir might trigger debris flow into the reservoir which will cause overtopping of Murum Dam. This study looked into the relationship of possible landsliding variables such as slope, elevation, aspect, curvature, basic geology and soil around Murum Dam Reservoir. For LSM, different thematic maps such as slope map, elevation map, curvature map, geology map and drainage buffer map are integrated in GIS according to weighted analysis method perform by several authors in previous literature studies. The LSM shows that there are few high susceptible areas and will be coupled with Transient Rainfall Infiltration and Grid-Based Regional Slope Stability Analysis (TRIGRS) in future to predict changes in factor of safety and pore water pressure of susceptible areas over a period of storm events.Â